Agitation Techniques to Enhance Drainage of Retained Hemothorax. (October 2021) - Makey, Ian A.; Das, Nitin A.; Jacob, Samuel; El-Sayed Ahmed, Magdy M.; Makey, Colleen M.; Johnson, Scott B.; Thomas, Mathew
Background . Retained hemothorax (RH) is a common problem in cardiothoracic and trauma surgery. We aimed to determine the optimum agitation technique to enhance thrombus dissolution and drainage and to apply the technique to a porcine-retained hemothorax. Methods . Three agitation techniques were tested: flush irrigation, ultrasound, and vibration. We used the techniques in a benchtop model with tissue plasminogen activator (tPA) and pig hemothorax with tPA. We used the most promising technique vibration in a pig hemothorax without tPA. Statistics . We used 2-sample t tests for each comparison and Cohen d tests to calculate effect size (ES). Results . In the benchtop model, mean drainages in the agitation group and control group and the ES were flush irrigation, 42%, 28%, and 2.91 ( P = .10); ultrasound, 35%, 27%, and .76 ( P = .30); and vibration, 28%, 19%, and 1.14 ( P = .04). In the pig hemothorax with tPA, mean drainages and the ES of each agitation technique compared with control (58%) were flush irrigation, 80% and 1.14 ( P = .37); ultrasound, 80% and 2.11 ( P = .17); and vibration, 95% and 3.98 ( P = .06). In the pig hemothorax model without tPA, mean drainages of the vibration technique and control group were 50% and 43% (ES = .29; P = .65). Discussion . In vitro studies suggested flush irrigation had the greatest effect, whereas only vibration was significantly different vs the respective controls. In vivo with tPA, vibration showed promising but not statistically significant results. Results of in vivo experiments without tPA were negative. Conclusion . Agitation techniques, in combination with tPA, may enhance drainage of hemothorax.